Toxicological Profiling of Unregulated Traditional Medicines in Unexplained Sudden Deaths Using LC-MS and Latent Class Analysis: A Forensic Autopsy-Based Study in South Sumatra - Fifia Ardinanti; Rizki Ayu; Sudarto (Phlox Institute: Indonesian Medical Research Organization, 2026)
Introduction: Unexplained sudden death (USD) presents a persistent diagnostic challenge in forensic medicine, especially in regions where consumption of unregulated traditional medicines (TM) is widespread. The toxicological contribution of unregulated TM to USD remains poorly characterized in Indonesia, where jamu use is prevalent and a large proportion of herbal products are unregistered. Methods: A forensic autopsy-based cross-sectional study was conducted on 120 USD cases at Hospital X, Palembang, South Sumatra, from January 2020 to December 2024. Postmortem femoral blood and liver tissue were screened by liquid chromatography-tandem mass spectrometry (LC-MS/MS) using a validated 85-compound panel covering alkaloids, heavy metals, pyrrolizidine alkaloids, aristolochic acid, and pharmaceutical adulterants. Sixty cases with verified TM use were compared with 60 non-TM user controls frequency-matched by age decade and gender. Latent class analysis (LCA) was applied for subgroup classification. Results: Alkaloids were detected in 75.0% of TM users versus 18.3% of controls (OR 13.36, 95% CI 5.62–31.72, p < 0.001). Pyrrolizidine alkaloids and pharmaceutical adulterants showed the highest discriminatory capacity (OR 15.55 and 21.00, respectively). Cardiac death was significantly more frequent in TM users (78.3% vs. 41.7%, p < 0.001). LCA identified three distinct toxicological subgroups: Class I (High Toxin Load, n=40), Class II (Moderate, n=36), and Class III (Low Toxin Load, n=44). Multivariate logistic regression, adjusted for age, BMI, hypertension, and toxicological findings, confirmed TM use as an independent predictor of cardiac death (adjusted OR 2.18, 95% CI 1.07–4.42, p = 0.031). Conclusion: These findings support the incorporation of TM-specific toxicological screening into standard forensic autopsy protocols and provide evidence for strengthened regulatory oversight of unregistered herbal products in Indonesia.